2013
DOI: 10.5539/ijef.v5n7p126
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy, Personal Financial Attitude, and Forms of Personal Debt among Residents of the UAE

Abstract: This paper examined financial literacy among a sample of individuals residing in the United Arab Emirates (UAE) and its relation to different forms of personal debt. These forms of personal debt include bank loans, borrowing from friends and/or family members, and borrowing through credit cards. We used a questionnaire distributed to a convenient sample of 412 individuals working for service organizations and residing across the UAE. Usable responses were about 45% of the sample and were subjected to descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 15 publications
3
33
0
7
Order By: Relevance
“…In the study, Al- Tamimi and Kalli (2009) found that financial literacy significantly influence the investment decisions of individual investors, which it relates to the use of financial services as the dependent variable. The different things are the researches, which are not consistent with Alqayadi Ibrahim (2013), which states that financial literacy is not a significant effect on the use of financial services. This is due to the policy in the country where the study sample (Alqayadi Ibrahim, 2013) is a non-resident population and the United Arab Emirates.…”
Section: Discussionmentioning
confidence: 81%
“…In the study, Al- Tamimi and Kalli (2009) found that financial literacy significantly influence the investment decisions of individual investors, which it relates to the use of financial services as the dependent variable. The different things are the researches, which are not consistent with Alqayadi Ibrahim (2013), which states that financial literacy is not a significant effect on the use of financial services. This is due to the policy in the country where the study sample (Alqayadi Ibrahim, 2013) is a non-resident population and the United Arab Emirates.…”
Section: Discussionmentioning
confidence: 81%
“…Financial literacy is the combination of investors' understanding of financial products and principles and their ability and dependability to consider financial risks and opportunities and make informed choices to take effective decisions aimed at improving their financial well-being (Ibrahim & Alqaydi, 2013). Furthermore, financial literacy is the ability to comprehend how money works in our daily lives and how people manage to invest it and how they offer it to each other.…”
Section: Literature Review 21 Definition and Concept Of Investment Amentioning
confidence: 99%
“…In the Arab environment, Ibrahim and Alqaydi (2013) studied financial literacy among a sample of residents in the United Arab Emirates and its relationship with personal debt. Their results pointed to the average level of financial literacy in UAE were lower than the average level reported in the literature.…”
Section: Financial Literacy and Its Consequencesmentioning
confidence: 99%